The relationship between typology and functional of flake tools from Bukit Bunuh 2010 site - AbdJalil, Siti Khairani; Abdullah, Jeffrey (School of Social Sciences, 2015)
Flake tool is one of the stone tools used by Paleolithic society which used stone as their technology. It is produced by flaking the core to get the flake. The flake that been used is known as flake tools. Flake tools found in Southeast Asia is said to be amorphous, which does not have a specific shape that can describe its function. So, this made it difficult for the typology classification of flake tool. However, many Paleolithic open sites have been classified based on flake tool morphology and technology, but the extent to which it represents the function has an issue. Therefore, usewear analysis was made using a flake tool from Bukit Bunuh’s site, which is Bukit Bunuh 2010. Bukit Bunuh was a meteorite impact area then it has been the source rocks suitable to be used as a tool by the Paleolithic society. In advance, the study was conducted by classifying flake tool typology according to morphological and technological. The results of this classification showed that there are four typologies identified as serrated, notched, pointed and retouched. Serrated can be divided into concave, convex and straight. While the notched been divided according to the number of notches. Retouched typology can be divided based on their edge trimming that is, alternate, alternating, direct, bifacial and inverse. Only pointed typology does not have subdivision. After the classification, the observation of the usewear of the flake tools had been done. As a result of these observations, there are several functions of the flake tools such as sawing, slicing, whittling, drilling, scratch and multiple functions. Almost all the flake tools were used for whittle except pointed and retouched type bifacial. Meanwhile, the serrated flake tools with type edge of convex, straight and retouched flake tools with type edge of direct has been widely used for a variety of activities compared with the other types of flake tools. So, this analysis indicated that most of flake tool used for various activities and also for specific functions. This shows that Paleolithic societies produced economic and multifunctional flake tools.